Letter from Herron and Baker Company to Ah Louis - Herron and Baker::::::author:::
Letter reads: 'Sept. 18; Ah Louis, San Luis Obispo: Dear [?] [You?] will please sack for us 60 sacks of the potatoes that have been dug 2 weeks or so to weigh about 105 to the sack and let us know what day the first of the week we can send a [?] for them. Yours and etc., Herron and Baker Co.'